The movement for global mental health : critical views from South and Southeast Asia - Sax, William Sturman, 1957-; Lang, Claudia (Social studies in Asian medicine., 2021)
In this volume, prominent anthropologists, public health physicians, and psychiatrists respond sympathetically but critically to the Movement for Global Mental Health (MGMH), which seeks to export psychiatry throughout the world. They question some of its fundamental assumptions: the idea that "mental disorders" can clearly be identified; that they are primarily of biological origin; that the world is currently facing an "epidemic" of them; that the most appropriate treatments for them normally involve psycho-pharmaceutical drugs; and that local or indigenous therapies are of little interest or importance for treating them. Instead, the contributors argue that labeling mental suffering as "illness" or "disorder" is often highly problematic; that the countries of South and Southeast Asia have abundant, though non- psychiatric, resources for dealing with it; that its causes are often social and biographical; and that many non-pharmacological therapies are effective for dealing with it. In short, they advocate a thoroughgoing mental health pluralism. Bron: Flaptekst, uitgeversinformatie